Pengaruh Model Contekstual Teaching and Learning (CTL) Terhadap Hasil Belajar PKn di Sekolah Dasar - Alwi, Elma; Abidin, Zainal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The recearch is aimed to know about the influence of using of Contextual Teaching and Learning (CTL) model toward the result of PKn student in grade V at SDN 13 Cingkariang Kecamatan Banuhampu Kabupaten Agam. The research design of the research is quasy exsperimental design. Sample of the research is class VA and VB. The coubting result of research of data that used is t test founded t count > ttable (4,015 > 2,011) at α level of 0.05. So that, it can be concluded that there is a significant influence in using Contextual Teaching and Learning (CTL) model toward the result of student’s PKn study in grade V SDN 13 Cingkariang Kecamatan Banuhampu Kabupaten Agam.  Keywords: Contextual Teaching and Learning (CTL), Learning Outcome, PKn